Lipid Accumulation and Injury in Primary Calf Hepatocytes Challenged With Different Long-Chain Fatty Acids - Zhang, Bingbing; Yang, Wei; Wang, Shuang; Liu, Runqi; Loor, Juan J.; Dong, Zhihao; Zhao, Yingying; Ma, Xinru; Xia, Cheng; Xu, Chuang (Frontiers in Veterinary Science, 2020)
Fatty liver disease is one of the most common disorders afflicting dairy cows during the postpartum period, and is associated with increased blood nonesterified fatty acid (NEFA) uptake by the liver. Major long-chain fatty acids (LCFA) in NEFA are palmitic (PA), palmitoleic (POA), stearic (SA), oleic (OA) and linoleic (LA) acid. In order to investigate the characteristics of lipid accumulation and injury caused by these NEFA, primary calf hepatocytes were isolated and challenged for 12 hours with 1.2 mmol/L PA, POA, SA, OA, LA or a mixture of these LCFA (NEFA). Compared with POA, OA, and LA, culture with PA and SA led to greater abundance of CCAAT-enhancer binding protein, glucose-regulated protein 78 mRNA, and stearoyl-CoA desaturase 1 mRNA along with greater concentrations of H2O2, malondialdehyde and reactive oxygen species (ROS). Although culture with POA, OA, and LA led to lower very low density lipoprotein (VLDL) concentration in cell culture medium, POA and OA led to greater concentrations of triacylglycerol, protein abundance of sterol regulatory element-binding protein 1c, fatty acid synthase, acetyl coenzyme A carboxylase 1, ApoB100 and sortilin 1 (Sort1).Compared with individual fatty acids, culture with NEFA led to an intermediate degree of lipid accumulation and hepatocytes damage. Overall, the data suggest that saturated fatty acids cause more severe oxidative and ER stress. However, unsaturated fatty acids cause serious lipid accumulation. Furthermore, a fatty acid balanced nutrient regulation was suggested useful improve liver health of transition period dairy cows.